Counting the hills : assessing development in Chittagong Hill Tracts - Rafi, Mohammad; Chowdhury, A. M. Raza (University Press, 2001)
Research report on the social, economic, demographic and environmental aspects of Chittagong Hill Tracts region; contributed articles.